The Early Days of the Euro Debt Crisis Revisited: Historical, Legal and Institutional Overview of the Role of the ECB in the Context of an Economic and Monetary Union in Mutation - Carmo, Rui do (2015)
This paper seeks to shed some light on the different stages of what ended up being a deep euro debt crisis of unforeseen proportions and the attempts of responses designed to address it in the context of an EU, unprepared to face its outcomes and implications. Our starting point is a quick overview of the historical, institutional and legal pathway that led to the set-up of the EMU, seeking to provide a better understanding of the backdrop for the on-going euro crisis and the several legal instruments put forward within and alongside the EMU framework to tackle it. Particular attention is given to the functions and goals originally attributed to the ECB and to some of the controversial steps this institution decided to take in order to address the debt crisis at its different stages. Finally, some lines of reflexion are proposed in light of the future challenges that we consider that an EMU in mutation inevitably entails.